Political Theology as critical theology - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2015)
This article attempts to draw the scope and content of contemporary Political Theology, based on a review of the 2013 publication titled, Political Theology: Contemporary challenges and future directions, edited by Francis Schüssler Fiorenza, Klaus Tanner and Michael Welker. The book is a collection of contributions which explore the contemporary content and potential future of the subject discipline. ‘Political Theology’ as critical theology and as a ‘theology with its face towards the world’ is committed to ‘justice, peace and the integrity of creation’ and is multifaceted. It represents a discipline with which theologians reflect on political-theological objectives across continents and paradigms. The article concludes with a brief investigation of the implications of insights offered in the book for the South African context (as part of the African continent).